2011
DOI: 10.1140/epje/i2011-11103-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the jamming behaviour of triblock copolymer solutions and triblock copolymer-anionic surfactant mixtures

Abstract: Photon correlation spectroscopy and rheological measurements are performed to investigate the microscopic dynamics and mechanical responses of aqueous solutions of triblock copolymers and aqueous mixtures of triblock copolymers and anionic surfactants. Increasing the concentration of triblock copolymers results in a sharp increase in the magnitude of the complex moduli characterising the samples. This is understood in terms of the changes in the aggregation and packing behaviours of the copolymers and the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The hindering of the bridge on the formation of the semibald micelle endows gel-1 and gel-2 with a relatively obvious boundary. Different from some thermogels formed by micelle jamming, 35,37 the thermogel of the PEG/PLGA block copolymer has the real physical cross-linking point of a hydrophilic bridge or a hydrophobic channel. The existence of the real cross-linking point explains why the thermogel could maintain its integrity for a long time after the formed physical hydrogel is put into a large amount of water.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hindering of the bridge on the formation of the semibald micelle endows gel-1 and gel-2 with a relatively obvious boundary. Different from some thermogels formed by micelle jamming, 35,37 the thermogel of the PEG/PLGA block copolymer has the real physical cross-linking point of a hydrophilic bridge or a hydrophobic channel. The existence of the real cross-linking point explains why the thermogel could maintain its integrity for a long time after the formed physical hydrogel is put into a large amount of water.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Some unique properties of PEG/polyester thermogels cannot be illustrated by the current theoretical models, such as the micelle jamming model, which has been confirmed as the internal structure of the thermogel of a commercial surfactant Pluronic composed of poly­(ethylene oxide)- b -poly­(propylene oxide)- b -poly­(ethylene oxide) (PEO-PPO-PEO). The jamming without any real connection among different micelles explains why the duration of the Pluronic thermogel after being put into a large amount of water is only overnight. Compared with the Pluronic thermogel, the obvious longer duration of even 3 months of PEG/polyester thermogel indicates some strong connection among the micelles instead of micelle jamming.…”
Section: Introductionmentioning
confidence: 98%
“…The addition of the anionic surfactant sodium dodecyl sulfate (SDS) to micellar Pluronic solutions, for example, leads to the formation of mixed micelles. These solutions have been studied using DSC, isothermal titration calorimetry (ITC), SLS and DLS, electromotive force (EMF), and surface tension measurements and rheology. …”
Section: Introductionmentioning
confidence: 99%
“…Experiments and a self consistent theory have shown that polydispersity affects the linear viscoelasticity of concentrated polymer solutions and melts [19]. In triblock copolymer Pluronic F127 suspensions, it is shown that the addition of an anionic surfactant, sodium dodecyl sulfate (SDS), breaks the large spherical micelles into smaller, anisotropic polydisperse micelles [20]. This speeds up the dynamics of the constituents of these mixtures and results in more efficient packing configurations, with the particle volume fraction for random close packing exceeding the value for suspensions of monodisperse hard spheres.…”
Section: Introductionmentioning
confidence: 99%